FORMULASI DAN UJI SIFAT FISIK LIP BALM ESKTRAK ETANOL BUAH STRAWBERRY (Fragraria Sp) - Mustika Sari, Rahayu (Journal of Pharmacy Tiara Bunda, 2022)
Lip balm is a preparation that is applied to the lips to function as a moisturizer by forming a layer of oil that does not mix on the surface of the lips. Strawberry (Fragraria) functions as an antioxidant and anti-inflammatory so that the strawberry fruit extract can be used as a moisturizer and will be maximized when used in the form of cosmetic products. The aim was to determine whether the ethanol extract of strawberry fruit (Fragraria) can be used in lip balm preparations and the difference in the ethanol extract concentration of strawberry fruit (fragraria) could affect the physical properties of lip balm preparations and determine the concentration of what lip balm preparations preferred by respondents. Strawberry fruit is obtained in the mountainous area of Tegal district. The extraction method used in this research is the maceration method with a concentration of 5%, 10% and 15%. The evaluation of lip balm preparations includes organoleptic test, pH test, irritation test, preference test, homogeneity test, smear test, melting point test. The results showed that the lip balm preparation of strawberry fruit extract (Fragraria) had no effect on the physical properties of the lip balm preparation. Formulas 1, 2 and 3 produce good physical properties, which include organoleptic tests, homogeneity tests, pH tests, melting point tests, irritation tests, and spreadability tests. Based on the preference test which includes color, aroma and moisture, formula 1 is the most preferred formula with a preference for color and aroma as much as 90% with the humidity level of 80%